2007
DOI: 10.1002/adem.200700007
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Solid Processing of Tailored Aluminium‐Lithium Alloys for Automotive Applications

Abstract: This paper describes the development and evaluation of thixoformable Al‐Li‐Mg‐based alloys performed at the collaborative research center SFB 289, RWTH Aachen. Scandium and zirconium were added to AlLi2.1Mg5.5 (A1420) with the aid of DoE (Design of Experiments), and precursor billets were manufactured by pressure induction melting (PIM). To evaluate the thixoformability of the synthesized alloys semi‐solid processed connecting rods were manufactured by the rheo container process (RCP). Subsequent heat treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Via heat treatment the mechanical properties of AA1420 * were improved significantly. In this way the tensile strength was increased to over 400MPa, the yield strength up to 250MPa, and the elongation to fracture to an average of 6.4%, almost three times higher than in the thixocast condition, [8]. Chemical analyses showed that the tie rods were manufactured homogeneously, [8].…”
Section: Rheo Container Process: Experiments and Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Via heat treatment the mechanical properties of AA1420 * were improved significantly. In this way the tensile strength was increased to over 400MPa, the yield strength up to 250MPa, and the elongation to fracture to an average of 6.4%, almost three times higher than in the thixocast condition, [8]. Chemical analyses showed that the tie rods were manufactured homogeneously, [8].…”
Section: Rheo Container Process: Experiments and Resultsmentioning
confidence: 96%
“…In this way the tensile strength was increased to over 400MPa, the yield strength up to 250MPa, and the elongation to fracture to an average of 6.4%, almost three times higher than in the thixocast condition, [8]. Chemical analyses showed that the tie rods were manufactured homogeneously, [8]. To investigate the improvement potentials of the heat treatment, sectioned samples of the connecting rod were solution-annealed (24h at 460°C), quenched in water and subsequently aged for various times in an oil bath at different temperatures (140°C, 160°C, 180°C) at the Swiss Federal Institute of Technology (ETH) Zurich.…”
Section: Rheo Container Process: Experiments and Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…6,7) SSMF is achieved through forming the component by dies at the semisolid temperature based on the semi-solid billets. 8) The fabrication of the semi-solid billet with the small and spherical grains is the guarantee to realize a successful SSMF. Many methods have been proposed to prepare the high-quality semi-solid billets, including the mechanical and electromagnetic stirring, 9) gas-induced semi-solid process, 10) cooling slope, 11) strain-induced melting activation (SIMA), 12) mechanical vibration, 13) and recrystallization and partial melting (RAP).…”
Section: Introductionmentioning
confidence: 99%